2017
DOI: 10.1103/physrevb.96.125147
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and polar catastrophe at the surface of LixCoO2 studied by angle-resolved photoemission spectroscopy

Abstract: We report an angle-resolved photoemission spectroscopy (ARPES) study of Li x CoO 2 single crystals which have a hole-doped CoO 2 triangular lattice. Similar to Na x CoO 2 , the Co 3d a 1g band crosses the Fermi level with strongly renormalized band dispersion while the Co 3d e ′ g bands are fully occupied in Li x CoO 2 (x=0.46 and 0.71). At x=0.46, the Fermi surface area is consistent with the bulk hole concentration indicating that the ARPES result represents the bulk electronic structure. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Importantly, no antiband crossing is found from the second derivative EDM in the -M direction, down to 0.8 eV of the binding energy. Next, comparing our experimental band structure with the available ARPES data on these type of systems, analogous to Na x CoO 2 [27,28,31] and Li x CoO 2 [32], we could also observe only one circular-shaped hole pocket from the Fermi surface map. Most importantly, in agreement with the previous report on K 0.62 RhO 2 [29], we identified an antiband crossing at ≈0.4 eV below E F in the -K direction.…”
Section: Resultsmentioning
confidence: 74%
“…Importantly, no antiband crossing is found from the second derivative EDM in the -M direction, down to 0.8 eV of the binding energy. Next, comparing our experimental band structure with the available ARPES data on these type of systems, analogous to Na x CoO 2 [27,28,31] and Li x CoO 2 [32], we could also observe only one circular-shaped hole pocket from the Fermi surface map. Most importantly, in agreement with the previous report on K 0.62 RhO 2 [29], we identified an antiband crossing at ≈0.4 eV below E F in the -K direction.…”
Section: Resultsmentioning
confidence: 74%
“…However, while experimentally the top of holelike band near K is at around 0.25 eV below E F , the DFT calculations suggest that these bands cross E F . Next, comparing our experimental band structure with the available ARPES data on these type of systems, analogous to Na x CoO 2 [27,28,31] and Li x NaCo 2 [32], we could also observe only one circular-shaped hole pocket from the Fermi surface map. Most importantly, in agreement with the previous report on K 0.62 RhO 2 [29],…”
mentioning
confidence: 75%
“…In the ARPES study of Okamoto et al [32], essentially the hole doping effects of reduced Li are observed on the bulk Fermi surface and the results were primarily interpreted in terms of the bulk band structure and the above mentioned surface polar discontinuity arguments. The additional Li-related surface band pocket near Γ we predict here was not observed but this may simply be because this surface band is not broad enough to dip below the Fermi level when the Li concentration on the surface is not high enough.…”
Section: Discussion Of Experimental Evidencementioning
confidence: 99%
“…While several angular resolved electron spectroscopy (ARPES) and scanning tunneling microscopy studies (STM) have been published in the past [3,[28][29][30][31][32] for both Li x CoO 2 and Na x CoO 2 they were generally focused on the bulk rather than on the search for surface states, which may thus have been missed. As pointed out at various places in our paper, the condition for finding a metallic 2DEG is that the Li concentration on the surface is sufficiently high to allow for the band width of the Li surface band to overlap with the CoO 2 surface band to create a semimetallic situation.…”
Section: Discussion Of Experimental Evidencementioning
confidence: 99%